Herb-Derived Products: Natural Tools to Delay and Counteract Stem Cell Senescence. (8th October 2020) - Abruzzo, Provvidenza M.; Canaider, Silvia; Pizzuti, Valeria; Pampanella, Luca; Casadei, Raffaella; Facchin, Federica; Ventura, Carlo
Abstract : Cellular senescence plays a very important role in organismal aging increasing with age and in age-related diseases (ARDs). This process involves physiological, structural, biochemical, and molecular changes of cells, leading to a characteristic trait referred to "senescence-associated secretory phenotype (SASP)." In particular, with aging, stem cells (SCs) in situ exhibit a diminished capacity of self-renewal and show a decline in their functionality. The identification of interventions able to prevent the accumulation of senescent SCs in the organism or to pretreat cultured multipotent mesenchymal stromal cells (MSCs) prior to employing them for cell therapy is a main purpose of medical research. Many approaches have been investigated and resulted effective to prevent or counteract SC senescence in humans, as well as other animal models. In this work, we have reviewed the chance of using a number of herb-derived products as novel tools in the treatment of cell senescence, highlighting the efficacy of these agents, often still far from being clearly understood.